Cardiac Surgeons Highlight the Need for Innovation Stewardship: Noteworthy in 2022. (June 2023) - Netsanet, Adom; Cotton, Jake; Suarez-Pierre, Alejandro; Hoffman, Jordan; Aftab, Muhammad; Reece, Brett; Rove, Jessica Y.
Modern cardiac surgery has rapidly evolved to treat complex cardiovascular disease. This past year boasted noteworthy advances in xenotransplantation, prosthetic cardiac valves, and endovascular thoracic aortic repair. Newer devices often offer incremental design changes while demanding significant cost increases that leave surgeons to decide if the benefit to patients justifies the increased cost. As innovations are introduced, surgeons must continuously aim to harmonize short- and long-term benefits with financial costs). We must also ensure quality patient outcomes while embracing innovations that will advance equitable cardiovascular care.